2020
DOI: 10.1002/chem.202000391
|View full text |Cite
|
Sign up to set email alerts
|

Cp*RuCl‐Vinyl Carbenes: Two Faces and the Bifunctional Role in Catalytic Processes

Abstract: Ruthenium vinyl carbenes derived from Cp/Cp*RuCl‐based complexes (Cp=cyclopentadiene, Cp*=1,2,3,4,5‐pentamethylcyclopentadiene) have been routinely invoked as key intermediates in tandem reactions involving a carbene/alkyne metathesis (CAM). A priori, these intermediates resemble the Grubbs‐type family of catalysts, but they exhibit a completely different reactivity pattern that few, if any, other catalytic system can reproduce so far. The reactivity of these species with α‐unsubstituted and α‐substituted alky… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 95 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…78 Once again, the conclusions drawn from our experimental data tally well with the computational results of Saáand coworkers, who suggested that the vinylcarbene species formed by CAM evolve via a "hydride transfer" mechanism. 19,20 In addition, our own computations of the C−H insertion pathway populated by ruthenium α-oxocarbene complexes such as D (Scheme 2) showed a very obtuse angle between the carbene center and the incoming reaction partner. 81 ■ CONCLUSIONS gem-Hydrogenation is a conceptually novel mode of H 2 transfer to an organic substrate, which our group was able to discover after a century of intense research devoted to catalytic hydrogenation in innumerous academic as well as industrial laboratories.…”
Section: ■ Results and Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…78 Once again, the conclusions drawn from our experimental data tally well with the computational results of Saáand coworkers, who suggested that the vinylcarbene species formed by CAM evolve via a "hydride transfer" mechanism. 19,20 In addition, our own computations of the C−H insertion pathway populated by ruthenium α-oxocarbene complexes such as D (Scheme 2) showed a very obtuse angle between the carbene center and the incoming reaction partner. 81 ■ CONCLUSIONS gem-Hydrogenation is a conceptually novel mode of H 2 transfer to an organic substrate, which our group was able to discover after a century of intense research devoted to catalytic hydrogenation in innumerous academic as well as industrial laboratories.…”
Section: ■ Results and Discussionmentioning
confidence: 91%
“…These experimental and spectroscopic data concur with the conclusions drawn by Saá and co-workers, who studied the fate of ruthenium vinylcarbene intermediates generated by CAM in silico. , These authors suggested that the η 3 -bound isomer accounts for the downstream chemistry; it draws its higher reactivity from an out-of-plane distortion that causes an electronic perturbation and, at the same time, renders the site sterically more exposed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…May [18] described the isolation and mechanistic relevance of ring-fused cyclopropenes with rhodium catalysts (path I). Some of us [12a] postulated the formation of a rhodium(I) η 3vinylcarbene intermediate through a [ π 2 s + π 2 a ] addition that subsequently evolves to the rhodium(I) η 1 -vinylcarbene, a proposal also shared by Saá [19] in their intermolecular Rucatalyzed CAM cascade processes (path II, Scheme 4). Yu and Xu [20] proposed a 5-exo-dig cyclization leading to a very reactive zwitterionic vinyl cationic species that upon a Rh-1,3-shift converts to the rhodium(II) η 1 -vinylcarbene (path III).…”
Section: The Functionalization Of Cà H Bonds By Transition Metal-mentioning
confidence: 99%